ATENÇÃO FARMACÊUTICA A IDOSOS PORTADORES DE DOENÇAS CRÔNICAS NO ÂMBITO DA ATENÇÃO PRIMÁRIA À SAÚDE - Edimar FERREIRA JÚNIOR; Almária Mariz BATISTA (Federal Council of Pharmacy, 2018)
Pharmaceutical Care is a practice developed in the context of Pharmaceutical Assistance, comprising attitudes, ethical values, behaviors, skills, commitments, and co-responsibilities in disease prevention, health promotion and recovery, in an integrated way to the health workers team. It focuses on the drug user, health education, pharmaceutical orientation, activities systematic recording, results in measurement and evaluation, in the search for a satisfactory response to the pharmacological therapy. The present study aimed to review the relevant literature on Pharmaceutical Care in the context of elderly with chronic diseases attended by primary health care. A bibliographic review was carried out, using the databases NCBI (via Pubmed), Web of Science, Scopus, and LILACS. Without the pharmacist performance, the medication and care related to its use are disorderly and disqualified at the SUS. There were significant problems at all points involving pharmacotherapy, such as adherence, polypharmacotherapy, self-medication, drug problems and drug interactions. Pharmaceutical Care in the context of elderly health problems is essential for the strengthening of adherence to treatment, expenses reduction, medicines rational use promotion, drug problems reduction, disease information.